Degradation of Linear Alkyl Benzene Using an Immobilized Nano TiO2 Photocatalytic Reactor: Process Analysis and Modeling. Issue 1 (30th November 2015) - Zangeneh, Hadis; Zinatizadeh, Ali Akbar Lorestani; Feyzi, Mostafa
Abstract : An immobilized nano TiO2 photocatalytic reactor under UVA (365 nm) irradiation was used for the degradation of linear alkyl benzene (LAB) in industrial wastewater. The performance of the photocatalysis was analyzed and modeled by response surface methodology. The effects of chemical oxygen demand (CODin ), reaction time and initial pH on the COD removal efficiency, specific COD removal rate, biochemical oxygen demand (BOD)5 /COD ratio, and final pH were determined. The enhancing effects of H2 O2, O3, and O3 /H2 O2 on the performance of the photocatalysis process were also investigated. The maximum BOD5 /COD ratio and COD removal efficiency for the photocatalytic reaction alone were found to be 0.45 and 37%, respectively, at an initial COD of 400 mg/L and pH 3, while the photocatalytic process induced by H2 O2, O3, and O3 /H2 O2 showed maximum COD removal efficiencies of 50, 60, and 69%, respectively. The gas chromatography–mass spectrometry results also showed a noticeable reduction in the organic content of the wastewater during the process. As the photocatalytic process was found time independent due to the catalyst poisoning, the catalyst surface regeneration was carried out by sequence aeration and ozonation. As a result, the procedure could improve the process performance by about 12% increase in COD removal efficiency. The characterization of the prepared TiO2 photocatalyst was carried out by powder X‐ray diffraction, scanning electron microscopy, and atomic force microscopy. Abstract : An immobilized TiO2 photocatalytic reactor under UVA (365 nm) irradiation was used for the degradation of linear alkyl benzene (LAB) industrial wastewater. The process is in fact very simple, it does not require any filtration or separation of the oxide slurry and it leads to complete pollutant mineralization. It could be an appropriate pretreatment method prior to a biological treatment process.